Analysis of Performance Characteristics and Efficiency of Electric Car Battery Charging Using The Method (CC-CV) - Lubis, Muhammad Hanafi Sahar; Hasibuan, Arnawan; Fariadi, Dedi; Abdullah, Dahlan; Nasution, Fakhruddin Ahmad; Jannah, Misbahul; A. Z, Abdullah (VOCATECH: Vocational Education and Technology Journal, 2025)
AbstractThe growth of electric vehicles (EVs) continues to increase in line with the global awareness of the importance of using environmentally friendly energy. One of the main components in an EV system is the battery, which requires an efficient and safe charging system. The Constant Current–Constant Voltage (CC-CV) charging method is one of the most commonly used approaches, as it maintains stable current and voltage during the charging process. This study aims to design a battery charging system simulation for electric vehicles using the CC-CV method, analyze the charging performance characteristics, and evaluate its efficiency. The research method used is simulation with MATLAB/Simulink software. The research stages include literature review, problem identification, circuit simulation design, simulation implementation, and result analysis. A PI Controller is employed to precisely regulate current and voltage, along with State of Charge (SoC) and voltage sensors to monitor the battery condition in real-time. Simulation results show that the system is capable of automatically transitioning between Constant Current (CC) and Constant Voltage (CV) modes responsively and stably. In CC mode, charging occurs rapidly with constant current, while in CV mode, voltage is kept stable and current gradually decreases. The achieved charging indicating that the CC-CV method enables a fast, safe, and efficient charging process while minimizing the risks of overcharging and overvoltage. AbstrakPertumbuhan kendaraan listrik (electric vehicle/EV) terus meningkat seiring dengan kesadaran global terhadap pentingnya penggunaan energi ramah lingkungan. Salah satu komponen utama dalam sistem kendaraan listrik adalah baterai, yang memerlukan sistem pengisian daya yang efisien dan aman. Metode pengisian Constant Current–Constant Voltage (CC-CV) merupakan salah satu pendekatan yang paling umum digunakan karena mampu menjaga kestabilan arus dan tegangan selama proses pengisian. Penelitian ini bertujuan untuk merancang simulasi sistem pengisian daya baterai kendaraan listrik menggunakan metode CC CV, menganalisis karakteristik performa pengisian, serta mengevaluasi efisiensinya. Metode penelitian yang digunakan adalah simulasi menggunakan perangkat lunak MATLAB/Simulink. Tahapan penelitian meliputi studi literatur, identifikasi masalah, perancangan rangkaian simulasi, pelaksanaan simulasi, serta analisis hasil simulasi. Dalam perancangannya, digunakan PI Controller untuk mengatur arus dan tegangan secara presisi, serta sensor State of Charge (SoC) dan sensor tegangan untuk memantau kondisi baterai secara real-time. Hasil simulasi menunjukkan bahwa sistem mampu melakukan transisi otomatis antara mode Constant Current (CC) dan Constant Voltage (CV) secara responsif dan stabil. Pada mode CC, pengisian berjalan cepat dengan arus konstan, sedangkan pada mode CV, tegangan dijaga tetap dan arus menurun secara bertahap. Efisiensi pengisian daya yang dicapai menunjukkan bahwa metode CC-CV mampu memberikan proses pengisian yang cepat, aman, dan efisien, serta meminimalkan risiko overcharge dan overvoltage).